2012
DOI: 10.1080/15459624.2012.635133
|View full text |Cite
|
Sign up to set email alerts
|

Discomfort and Exertion Associated with Prolonged Wear of Respiratory Protection in a Health Care Setting

Abstract: The nature of discomfort and level of exertion associated with wearing respiratory protection in the health care workplace are not well understood. Although a few studies have assessed these topics in a laboratory setting, little is known about the magnitude of discomfort and the level of exertion experienced by workers while they deliver health care to patients for prolonged periods. The purpose of this study was to determine the magnitude of discomfort and level of exertion experienced by health care workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 26 publications
3
134
0
4
Order By: Relevance
“…Shenal et al 37 reported self-perceived discomfort using a visual analog scale and perceived exertion using the Borg scale from 27 HCWs (aged 24–65 years, 55% women) wearing different types of respirators and facial protection equipment during an 8-hour shift. Three N95 FFRs were included: 3M 1860 (cup shaped), 3M 8511 (cup shaped with exhalation valve, 3M, St. Paul, MN), and Kimberly-Clark PFR95170 (duckbill, Kimberly-Clark, Roswell, GA).…”
Section: Resultsmentioning
confidence: 99%
“…Shenal et al 37 reported self-perceived discomfort using a visual analog scale and perceived exertion using the Borg scale from 27 HCWs (aged 24–65 years, 55% women) wearing different types of respirators and facial protection equipment during an 8-hour shift. Three N95 FFRs were included: 3M 1860 (cup shaped), 3M 8511 (cup shaped with exhalation valve, 3M, St. Paul, MN), and Kimberly-Clark PFR95170 (duckbill, Kimberly-Clark, Roswell, GA).…”
Section: Resultsmentioning
confidence: 99%
“…The use of PPE can affect clinical performance by limiting manual dexterity, impairing hearing and communication, and causing discomfort for the user. [12][13][14][15] Hands-on practice allows the user to be better prepared to provide safe patient care while wearing PPE. A strategy that can be used to prepare health care providers to provide safe care in the emergency setting is the use of in situ simulation training sessions.…”
Section: Training and Fit Testingmentioning
confidence: 99%
“…27 Discomfort was routinely raised as a key factor limiting the practicality of the CDC and OSHA recommendations during the 2009 novel H1N1 influenza pandemic. 21,30,31 Psychologic manifestations of respirator wear, such as claustrophobia, may also be considered forms of discomfort, 32 and improper usage of these devices is relatively common, 26,33 such that it may lead to discomfort. In general, surgical masks are viewed as more comfortable than respirators.…”
Section: Current State Of Respiratory Protection In Health Carementioning
confidence: 99%
“…Based on recommendations issued by the IOM 21 and findings from its own respirator research in 2007 and 2008, 26,30,39 the Department of Veterans Affairs (VA) was prompted to improve the PPE practices used by its employees. VA is the largest integrated health care system in the United States and employs or oversees 180,000 HCP who use approximately 1.6 million respirators per year.…”
Section: Project Better Respiratory Equipment Using Advanced Technolomentioning
confidence: 99%